A two-level morphology of Malagasy - Dalrymple, M; Liakata, M; Mackie, L; Acad Sinica, I (2005)
We present a two-level model of Malagasy nominal and verbal morphology (Beesley and Karttunen, 2003), based primarily on the discussion of Malagasy morphology in Keenan and Polinsky (1998) and Randriamasimanana (1986). Words in Malagasy are built from roots by means of a variety of morphological operations such as affixation and reduplication. The present paper analyzes productive patterns of nominal and verbal morphology, describing genitive compounding and suffixation for nouns, and various derivational processes involving compounding and affixation for verbs.